Cardiac Contractility Modulation as bridge to recovery in a patient with advanced heart failure evaluated for left ventricular assist devices: a case report and review of literature - Francesca Menichetti; Marco Solari; Elisa Salvetti; Vincenzo Guarnaccia; Tommaso Girasole; Flavio Venturi; Attilio Del Rosso (Frontiers in Cardiovascular Medicine)
This case report illustrates the effects of CCM as a bridge to recovery in a patient who has been a candidate for LVAD. After CCM the patient hase become stable in NYHA class II, with no further acute HF episodes and a significant clinical and functional improvements. Consequently, the patient was no longer an LVAD candidate, as CCM had acted as a bridge to recovery, making the advanced HF designation no longer applicable. The ease of implantation, uneventful procedural recovery, extraordinary device longevity, and favorable risk profile all position CCM as an important tool in the treatment of advanced HFrEF patients candidate to LVAD therapy, serving as a bridge to recovery.Further large-scale randomized controlled trials are needed to confirm the long-term benefits of CCM therapy in this particular population subgroup, helping a better patient selection.